Trudovoy semestr-na otlichno! - Belsky, L; Potapov, V (Плакат СССР (Plakat), 1981)
Male and female Soviet construction workers standing to attention, amid scnees of infrastructure and red flags Original title: Трудовой семестр-на отлично! PO-1867